2018
DOI: 10.1039/c8ta02819b
|View full text |Cite
|
Sign up to set email alerts
|

Engineering onion-like nanoporous CuCo2O4 hollow spheres derived from bimetal–organic frameworks for high-performance asymmetric supercapacitors

Abstract: An asymmetric supercapacitor fabricated using onion-like nanoporous CuCo2O4 hollow spheres exhibits an energy density of 48.75 W h kg−1 and a power density of 37.5 kW kg−1, which can compete with Ni–MH batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(49 citation statements)
references
References 74 publications
2
47
0
Order By: Relevance
“…50 The Cu-2p scan also showed two strong photoelectron emissions de-convoluted at 935.4 eV and 955.3 eV, corresponding to the Cu-2p 3/2 and Cu-2p 1/2 electronic levels, respectively. 51,52 These are the characteristic peaks of Cu(II), and the Cu 2+ oxidized charge state in CuGa 2 O 4 exhibited a spin-orbit splitting energy separation of 19.9 eV which matched the previously reported values well. [51][52][53][54] The Ga-2p scan showed two peaks centred at 1118.18 eV and 1145.08 eV corresponding to Ga-2p 3/2 and Ga-2p 1/2 , respectively, as shown in Fig.…”
Section: Xps Analysissupporting
confidence: 88%
See 2 more Smart Citations
“…50 The Cu-2p scan also showed two strong photoelectron emissions de-convoluted at 935.4 eV and 955.3 eV, corresponding to the Cu-2p 3/2 and Cu-2p 1/2 electronic levels, respectively. 51,52 These are the characteristic peaks of Cu(II), and the Cu 2+ oxidized charge state in CuGa 2 O 4 exhibited a spin-orbit splitting energy separation of 19.9 eV which matched the previously reported values well. [51][52][53][54] The Ga-2p scan showed two peaks centred at 1118.18 eV and 1145.08 eV corresponding to Ga-2p 3/2 and Ga-2p 1/2 , respectively, as shown in Fig.…”
Section: Xps Analysissupporting
confidence: 88%
“…51,52 These are the characteristic peaks of Cu(II), and the Cu 2+ oxidized charge state in CuGa 2 O 4 exhibited a spin-orbit splitting energy separation of 19.9 eV which matched the previously reported values well. [51][52][53][54] The Ga-2p scan showed two peaks centred at 1118.18 eV and 1145.08 eV corresponding to Ga-2p 3/2 and Ga-2p 1/2 , respectively, as shown in Fig. 7c 51 , with an energy separation of 26.9 eV which matched the previously reported value well.…”
Section: Xps Analysissupporting
confidence: 88%
See 1 more Smart Citation
“…The authors supported that the superior electrochemical performance observed in these materials was possible due to the nanoporous nature of the shells, along with the high surface area available. In addition, the multi-shelled structure with nanometric width delivered an important synergistic effect between Cu and Co species in the spinel structure of the final material [142].…”
Section: Recent Advances In Complex Hollow Nanostructured Materials Fmentioning
confidence: 99%
“…For examples, Zhu et al prepared mesoporous NiCo 2 O 4 hollow spheres with PVP as a facile soft-template [26]. Ensafi et al designed onion-like CuCo 2 O 4 hollow microspheres with a diameter of about 1 μm by using bimetal-organic frameworks as a self-template [27]. The flexible multi-shelled soft templates such as vesicle are easily destroyed by changing parameters whereas the success for the conversion of single-shelled to multi-shelled hollow microspheres is limited for self-template method [28].…”
Section: Introductionmentioning
confidence: 99%